Meningkatkan Kemampuan Guru pada Pembelajaran Membaca Anak Disleksia - Irdamurni, Irdamurni; Kasiyati, Kasiyati; Zulmiyetri, Zulmiyetri; Taufan, Johandri (Jurnal Pendidikan Kebutuhan Khusus, 2018)
The objective of this study was to investigate reading instruction training for teaching teachers to teach reading student with dyslexia. Training mothods uses multi methods I.e lectures vary, demonstrations, exercises and assignments. The increased aspects related to the implementation of identification and assesment, development of modification lesson plan and individualized educational program. Futhermore, reading instruction for dyslexia includes strategy and learning media as assesment of learning for students with dyslexia. .